Learning from Tradition: Consumer Attitudes and Perceptions of Leaf and Plastic Food Wrapping and Packaging in Kumba, Southwest Cameroon - Aristide Guillaume Silapeux Kamda; Pricillia Anjeh; Gillian Asoba; Solange Nwobonche Chiakeh; Elizabeth Nebale; Francesca Baldi; Samuel Metugue; Fidelis Ebong; Chiara Frazzoli (Challenges)
Food contact materials release bioactive molecules that are potentially detrimental to health. Despite the relevance of this daily and repeated exposure, little attention is paid to single-use materials in contact with food. In Cameroon, despite the local tradition of using biodegradable and compostable leafy plants and the government’s decision to ban the use and marketing of plastics, they are still massively used in contact with food. The aim of this study was to explore the dynamics of the ongoing trend in the use of plastics for food handling. A cross-sectional study was conducted in March 2023 to investigate consumers’ perceptions of the benefits and drawbacks of plastics and traditional leaves as food contact materials. Two hundred consumers were interviewed at eight restaurants in Kumba municipalities through a structured questionnaire. The result of this study revealed that consumers considered that plant-based materials do not affect human health; they know that leaves, compared to plastics, are easier to dispose of and that plastic is an environmental hazard. Age and education turned out to significantly affect all the answers, while income did not. The current study highlights the need to provide clear and updated information on the long-term danger posed to health and the environment by plastics used to cook, store, protect, and transport food. Despite the numerous advantages and benefits of traditional leaves as food contact material, their traditional use by the population has been lost. Consumers in Cameroon are at a critical juncture in choosing biodegradable and compostable food contact materials. This transition can be accelerated if governments invest in actions and measures to curb and potentially reverse the widespread adoption of plastics as a symbol of modernity. Scientific and technological research should engage in the innovation of traditional plant-based materials. This local example is also intended to provide impetus for more global investment in traditional plant-based materials for food packaging to support sustainability and the planetary health agenda.